Anti‐tumor activities and apoptotic mechanism of ribosome‐inactivating proteins. Issue 3 (17th July 2015) - Zeng, Meiqi; Zheng, Manyin; Lu, Desheng; Wang, Jun; Jiang, Wenqi; Sha, Ou
Abstract: Ribosome‐inactivating proteins (RIPs) belong to a family of enzymes that attack eukaryotic ribosomes and potently inhibit cellular protein synthesis. RIPs possess several biomedical properties, including anti‐viral and anti‐tumor activities. Multiple RIPs are known to inhibit tumor cell proliferation through inducing apoptosis in a variety of cancers, such as breast cancer, leukemia/lymphoma, and hepatoma. This review focuses on the anti‐tumor activities of RIPs and their apoptotic effects through three closely related pathways: mitochondrial, death receptor, and endoplasmic reticulum pathways.